A set of miniaturized high-throughput library protocols for RNA sequencing - Waddling, Christopher (J Biomol Tech, 2020)
Several studies have demonstrated that increasing the number of biological replicates, even without increasing the total amount of sequencing, significantly improves experimental power to detect differentially expressed genes by RNA sequencing. However, the high cost of Illumina library production is a critical factor that limits the number of biological replicates performed, leading to underpowered experiments. Here we describe a set of protocols for Illumina library preparation from bulk RNA at miniaturized reaction volumes. Methods for preparation of long RNA-seq libraries (using either polyadenylated RNA enrichment or rRNA depletion) and small RNA-seq libraries were established on a mosquito pipetting robot that enables accurate liquid transfers at nanoliter to microliter volumes. Reaction volumes were scaled down between 5-fold and 20-fold compared to the kit manufacturers' protocols, while RNA input was kept constant. The miniaturized protocols were assessed for their performance with respect to numbers of transcripts detected and other standard RNA-seq quality metrics. Through a dramatic reduction in the cost of library preparation, this approach enables cost-effective high-throughput projects with increased numbers of biological replicates.